Sustainable Marketing, Corporate Risk, and Financial Value: A Bibliometric Analysis of Research Development, Knowledge Structure, and Future Directions - Mahayanti Fitriandari; Ade Maharini Adiandari; Yananto Mihadi Putra; Lucky Nugroho (Publikasi Indonesia, 2026)
Sustainable marketing has evolved from an environmental communication approach into a strategic organizational capability that integrates sustainability principles with long-term business performance. Despite the growing body of literature, the relationships among sustainable marketing, corporate risk, and financial value remain fragmented, with limited understanding of their intellectual structures and research trajectories. This study aimed to analyze research development, identify the knowledge structure, and propose future research directions concerning sustainable marketing, corporate risk, and financial value. A bibliometric performance analysis and science mapping approach were employed using 156 English-language articles and review papers indexed in the Scopus database from 2000 to 2026. The analysis examined publication trends, citation performance, influential authors, journals, countries, keyword co-occurrence, thematic evolution, and co-citation networks. The findings revealed a substantial increase in publications after 2019, indicating growing scholarly interest in the field. Five major thematic clusters were identified, emphasizing sustainability-driven performance, strategic green marketing, responsible supply chains, financial performance mechanisms, and firm value supported by green technologies. However, the literature remains predominantly focused on broad firm-performance indicators, while corporate risk and specific financial value measurements remain relatively underexplored. The study concludes that sustainable marketing should be regarded not only as a strategy for enhancing competitive advantage and financial performance but also as an organizational capability for mitigating corporate risk and strengthening long-term resilience. Future research should employ more precise financial indicators and integrate risk-oriented perspectives to provide a deeper understanding of sustainable value creation.